2011
DOI: 10.1111/j.1600-0684.2011.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

A case report of spontaneous opening of congenitally fused labia in a female common marmoset (Callithrix jacchus) followed by pregnancy and birth of twins

Abstract: A first case of spontaneous opening of congenitally fused labia (CFL phenotype) in a captive common marmoset followed by pregnancy and birth is presented here. The occurrence of this phenotype has been previously published in captive marmosets, but so far the etiology is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In cases where the sex of the female’s cotwin was reported, it was universally a male, and karyotyping or genotyping of females presenting with atypical genitalia revealed the presence of Y chromosomes in lymphocytes or Y chromosome-associated zinc-finger protein (Y-ZFP) [ 25 , 26 ]. Endocrine analyses of females indicated normative ovarian function including progesterone profiles consistent with ovulatory cycles [ 25 , 61 , 62 ] and low levels of testosterone [ 25 ] and its metabolic precursor androstenedione [ 62 ]. Ultrasound or post-mortem analyses revealed female-typical structures in the fallopian tubes, uterine horns and uterus, cervix, and vagina, ovaries that displayed primary and secondary follicles and corpora lutea, and no signs of testicular tissue [ 24 , 25 , 61 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the sex of the female’s cotwin was reported, it was universally a male, and karyotyping or genotyping of females presenting with atypical genitalia revealed the presence of Y chromosomes in lymphocytes or Y chromosome-associated zinc-finger protein (Y-ZFP) [ 25 , 26 ]. Endocrine analyses of females indicated normative ovarian function including progesterone profiles consistent with ovulatory cycles [ 25 , 61 , 62 ] and low levels of testosterone [ 25 ] and its metabolic precursor androstenedione [ 62 ]. Ultrasound or post-mortem analyses revealed female-typical structures in the fallopian tubes, uterine horns and uterus, cervix, and vagina, ovaries that displayed primary and secondary follicles and corpora lutea, and no signs of testicular tissue [ 24 , 25 , 61 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the phenomenon remains unclear, and to date, there are no other publications, with the exception of two previous small reports from our own group. One of these studies suggested a possible genetic link, and the case study has shown that the opening of the labia may be delayed in affected females, and that the opening occurs spontaneously, not through a forced entry from a sexually active male partner; subsequent pregnancy and birth in the same case study demonstrated normal function of the internal reproductive organs. Two publications from other groups have reported similar cases.…”
Section: Introductionmentioning
confidence: 50%
“…Since in marmoset this condition is not associated with an impaired reproductive function, once the vagina is wide enough open, it is unclear if it needs to be treated. It has, however, been routine practice in DPZ to surgically open post‐pubertal females which are intended for breeding, as mentioned in the Introduction.…”
Section: Discussionmentioning
confidence: 99%
“…The CFL syndrome was described in an elderly woman (6) and in common marmosets (5,7). This phenotype in heifers was reported by Oettlé and Coubrough (8) and Balasubramanian et al (9) and recently in a calf (10).…”
Section: Introductionmentioning
confidence: 70%
“…The congenitally fused labia (CFL) syndrome is defined as a variable occlusion of the labia majora by connective tissue (5). The CFL syndrome was described in an elderly woman (6) and in common marmosets (5,7).…”
Section: Introductionmentioning
confidence: 99%